Case report: Lymph node metastasis of pelvic alveolar rhabdomyosarcoma diagnosed by fine needle aspiration cytology - Hu, Xinyu; Huang, Chenxin; Li, Qiyuan; Wu, Baolin; Yue, Chuyun; Su, Xueying (Frontiers in Oncology, 2024)
Rhabdomyosarcoma (RMS) is a common soft tissue malignant tumor, especially in young patients. Alveolar rhabdomyosarcoma (ARMS) is a subtype of RMS that is prevalent in adolescents. This malignant tumor usually develops in the extremities and can also involve the trunk, perineum, and pelvis. Now, we report a rare case of pelvic lymph node metastatic alveolar RMS in a young patient, which was determined by fine needle aspiration cytology (FNAC). To the best of our knowledge, this is the first case in which the definite diagnosis of ARMS was initially made by FNAC.